Nakagami parametric image for evaluation of the degree of thermal denaturation inside porcine liver induced ex vivo by radiofrequency ablation. (21st February 2023) - Takeuchi, Michio; Sakai, Toshihiko; Oshima, Yusuke; Kojima, Yasuhiro; Mori, Kenji; Omura, Masaaki; Nagaoka, Ryo; Hasegawa, Hideyuki
Abstract: In an RF ablation procedure for treating hepatocellular carcinoma and metastatic liver cancer, plucking out an ablation antenna from incompletely cauterized tumor tissues can cause neoplastic seeding; hence, it is demanded to properly evaluate the thermal denaturation of tumor tissue before plucking out the antenna. In the present ex vivo study, we show that the degree of thermal denaturation inside porcine liver tissue induced with RF current heating can be evaluated by binarized two-dimensional Nakagami parametric image indicating the weighted average of the Nakagami shape parameter m . Moreover, we present that the pre-Rayleigh distribution is dominant in ultrasonic backscattered envelopes obtained from incompletely cauterized liver tissue, whereas the Rayleigh distribution is dominant in those obtained from completely cauterized liver tissue which has coagulative necrosis region. The result indicates that the change in scatterer distribution would be occurred inside liver tissue by coagulative necrosis caused by RF current heating in this study.